Sociocritical paradigm in research - Loza Ticona, Renzi Marilu (2020)
This article aims to analyze the socio-critical paradigm in its relationship with scientific research, which is why the paradigm is previously defined as the representation of the commitment of the members of a scientific community with a way of exercising or guiding scientific practice. Likewise, it seeks to conceptualize the socio-critical paradigm, which is based on social criticism with a tendency to self-reflection, understanding that knowledge is built on the basis of concerns that arise from the needs of certain social groups (Maldonado, 2018), where Unlike the positivist paradigm, the researcher is no longer just an observer to become a generator of change that facilitates social transformations. On the other hand, the origins, position of authors, characteristics, principles and applications in different specialties are analyzed. Finally, the conclusions seek to reflect on the applicability of the socio-critical paradigm in our society.